The Training System of the Royal Hungarian Police after its Nationalisation (1920) - Sallai, János (Magyar Rendészet, 2017)
Nationalisation (1919) was a decisive moment in the life of the Hungarian Police Force, after which, modelled on the Budapest police force, the unified Royal Hungarian State Police was created. After the nationalisation, the leadership of the Ministry of the Interior and of the Police Force paid special attention to the training and supply of the staff. This included the Prime Minister’s decree that regulated the police positions to be filled, the system of training for police non-commissioned officers, the range of theoretical and practical knowledge to be taught, the system of training courses and the examination requirements.